PENGARUH SUNSET POLICY DALAM PENERIMAAN PAJAK Studi Kasus Pada Kantor Pelayanan Pajak Pratama â€œXâ€ di Bandung - Soddin Mangunsong (Jurnal Akuntansi, 2009)
Sunset Policy is one of government regulation that give facility about tax to old tax payer and new tax payer. The implementation of that regulation is abolish the tax administation punishment (in this context is interest). The basic concept of sunset policy is self assesment system, which is tax payer is trusted to count, to calculate, to pay, and to report the amount of the tax payable by themselves according to the act or law related about it. The purpose of this research is how to know about the influence of the sunset policy to the tax receive. The method whis is use in this research is analitycal descriptive, using simple least square method : Y = a + bX. This research use data about tax period from 2003 until 2007, and the number of the tax payer is 56.104. This tax payer are divided into 2 groups, the first group is private tax payer and their number are 49.137. The second group is corporate tax payer and their number are 6.967. Keywords : Tax is from citizens and for citizens.